Wacana Berita Kekerasan Santri di Temanggung Pada Media Republika Online dan Kompas.com Ediisi 11 s.d 13 September 2023 - Muhammad Nurul Huda; Robi’ah Machtumah Malayati (Millatuna: Jurnal Studi Islam, 2024)
In every news reporting, online media platforms harbor their respective ideologies. In this regard, Republika Online and Kompas.com also possess their own ideologies in delivering information to the public. The textual structure and discourse of each media outlet differ based on the ideology adhered to by the respective media. In 2023, numerous incidents of violence against children occurred within the realm of education. One of them is the case of violence against Islamic boarding school students in Temanggung Regency, Central Java. Acts of violence can lead to physical and mental disturbances in children, as evidenced by the case of violence against students at an Islamic boarding school in Temanggung Regency, which resulted in the death of one of the students. There are two issues examined in this thesis: how Republika Online and Kompas.com, online media platforms, employ textual structures in presenting news about violence against Islamic boarding school students from September 11th to 13th, 2023, and how the discourse of Republika Online and Kompas.com is constructed in presenting news about violence against Islamic boarding school students from September 11th to 13th, 2023. To address these two issues, the researcher employs a qualitative descriptive approach. The method utilized by the researcher is discourse analysis, following Teun A. Van Dijk's method, in "Discourse of News on Violence Against Islamic Boarding School Students in Temanggung in Republika Online and Kompas.com from September 11th to 13th, 2023". In this research, it is concluded that the textual structures of Republika Online and Kompas.com tend to marginalize the perpetrators in their reporting. In Kompas.com's reporting, the tendency is to implicitly marginalize the perpetrators, whereas Republika Online tends to explicitly marginalize them. The ideology of Republika Online highlights the Islamic aspect, while Kompas.com is characterized by humanism. Keywords: News Discourse, Violence against Students, Republika Online, Kompas.com.